Chapter Leonardo da Vinci a Piombino: progetti di ammodernamento delle fortificazioni del litorale toscano - BERTOCCI, Stefano (Territori, 2023)
The paper describes a research on Leonardo da Vinci's activity as a military architect in Piombino, Tuscany, in the early years of the 16th century. These studies use modern digital survey technologies in order to recognize if, in the remains of the town's defensive system, there are still traces of the intervention carried out in Leonardo's time, and integrate these data with the analysis of historical-documentary sources and the results of recent archaeological and stratigraphic analyses. The achieved results were finally compared with Leonardo da Vinci's drawings, obtaining some interesting feedback.